Health Care Reforms that Serve the Poor - Koch-Weser, Caio K. (World Bank, Washington, DC, 2013)
This report presents the chairman Bruntland speech on the remarkable achievements in health, nutrition, and population (delivered at the XII Malente Symposium of the Drager Foundation in Lubec). There have been greater gains in life expectancy and greater decreases in birth rates throughout the world in the past four decades than during the entire previous four centuries. In his speech chairman has cite few achievements such as: 1) people all over the world live almost 25 years longer today than they would have lived at similar income levels in 1900; 2) there have been huge gains in infant mortality: the proportion of children who die before reaching age five is now less than half the level it was in 1960; 3) contraceptive use in low- and middle-income countries rose from 10 percent of married couples in the mid- 1960s, to 55 percent in 1990; and as a result of this and other factors; and 4) on average, women choose (and are able to act on this choice) to have three children each, down from five in 1960. Even in his speech chairman points that enormous progress have been made in understanding the causes of diseases, and in developing effective preventive and curative interventions such as immunization and antibiotics, but still there are challenges in the health sector, and policy option to channel scarce resources to the poor.